2013
DOI: 10.1038/modpathol.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of KRAS and PIK3CA mutations, MET and PTEN expression in primary tumors and corresponding metastases in colorectal cancer

Abstract: Metastasis is the main cause of mortality in patients with colorectal cancer. However, most of the targeted therapies and predictive molecular biomarkers were developed based mainly on primary tumors. The current study was conducted to determine the degree of discordance between potential predictive and/or prognostic molecular markers in primary colorectal tumors and corresponding metastases, as this could have an impact on the efficacy of targeted therapies in the advanced colorectal cancer. KRAS, PIK3CA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 68 publications
8
42
4
Order By: Relevance
“…It has been suggested that only PIK3CA mutations in exon 20 negatively affect the efficacy of EGFR-targeted therapies in patients with KRAS WT. 26 Although our findings clearly show our study was underpowered to detect a prognostic effect of PIK3CA mutations, they also lend support to a previous hypothesis, 27 suggesting that PIK3CA mutation in exon 9 segregates with KRAS mutations; the latter was an exclusion criterion for enrollment into the study.…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that only PIK3CA mutations in exon 20 negatively affect the efficacy of EGFR-targeted therapies in patients with KRAS WT. 26 Although our findings clearly show our study was underpowered to detect a prognostic effect of PIK3CA mutations, they also lend support to a previous hypothesis, 27 suggesting that PIK3CA mutation in exon 9 segregates with KRAS mutations; the latter was an exclusion criterion for enrollment into the study.…”
Section: Discussionsupporting
confidence: 82%
“…Since MET gene amplification in CRC has been previously reported,39 42 43 we also analysed MET gene copy number variations in CRC cell lines as well as NM, PC and LM tissues. Although MET expression was upregulated in MSS cell lines and 5-aza-dC-treated cell lines, MET gene copy number was not significantly different between MSI and MSS cell lines, as well as between CRC cell lines treated with the 5-aza-dC and non-treated cells (see online supplementary figure S6A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, neither MET host promoter methylation nor the host MET transcript correlated with MET protein expression; rather it was regulated by the methylation status of the LINE-1 element. With regards to the activation mechanism of MET expression in CRC, MET gene amplification has been reported previously,39 42 43 but there has been a lack of consensus on copy number variations and disease pathogenesis due to differences in analytical methods and the MET gene locus interrogated in these previous articles. In our study, MET gene copy numbers were significantly higher in primary CRC and liver metastasis compared with normal mucosa, while no significant differences were observed between matched primary CRC and liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown discordant mutation status between primary tumors and corresponding metastasis in a proportion (5%–30%) of CRC patients [3], [4], [5], [6]. Furthermore, recent studies suggest that acquired resistance is partly achieved by the selection of pre-existing minor sub-clones harboring mutations conferring resistance to anti-EGFR therapy [7], [8].…”
Section: Introductionmentioning
confidence: 99%